Virtual Monitoring of the 3d Movement of a Mobile Object, Using Unity - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2022)
This article presents the design of a real-time graphic representation system using UNITY 3D, this is a graphic engine for the development of a multiplatform video games in 2D / 3D, its potential to work in real time make it ideal for this application as a means of representation and monitoring in virtual reality, the main objective is to monitor the position and activities of one or more moving objects in a house, hospital, building, school, etc. The applications are diverse. The goal of this article as an initial stage is to obtain the monitoring of the position in real time of the activities of an object in motion in 3D, which will be sending information wirelessly to the UNITY 3D graphics engine and evaluate the relevance of using this graphic engine, considering its portability, versatility, free use and open source. © 2022 IEEE.